Aortic stenosis with impaired ventricular function manifests impaired cardiac metabolism: implications for prognosis and surgical intervention. (22nd September 2015) - Ashrafian, H; Howell, NJ; Ormerod, J; Hammer, F; Drury, N; Steeples, V; Lygate, C; Frenneaux, MP; Pagano, D; Watkins, H
Abstract : Introduction: It is increasingly recognised that energy deficiency contributes to the pathogenesis of left ventricular hypertrophy (LVH) and heart failure (HF). To delineate the metabolic mechanisms contributing to the transition from LVH to HF and to relate these to the operative risk of aortic valve replacement (AVR) in aortic stenosis (AS), the cardiac metabolic transciptome was studied at progressive stages in a murine model of AS and in patients with advanced AS with indices of HF. Methods: The expression pattern of master metabolic transcription factors (eg, PGC-1α and PPARα) and their downstream metabolic pathways were assessed in mice having undergone transverse aortic constriction at progressive stages of acute left ventricular pressure overload, compensated LVH and LVH plus HF, corresponding to the phases of AS. This pattern of metabolic changes was compared with patients undergoing AVR surgery for advanced AS with haemodynamic features of HF. Mass spectrometry was used to assess high-energy phosphate species and other metabolites in the myocardium. Results: Although acute pressure overload was not accompanied by any significant changes in the metabolic transcriptome, compensated LVH and the transition to HF were accompanied by consistent downregulation of master transcriptional regulators controlling mitochondrial biogenesis/fatty acid metabolism (eg, PGC1α, PPARα and ERRα) and their downstream pathways (eg, CPT-1; fig 1 ). A corresponding pattern of energetic compromise (including reduced ATP/ADP) was observed in advanced AS with HF (fig 2 ). Conclusions: Our findings suggest that the downregulation of cardiac metabolism resulting from the observed progressive downregulation of the cardiac metabolic transcriptome during the transition from LVH to HF may contribute to the pathogenesis of ventricular dysfunction and predispose patients to adverse surgical outcomes. A combination of timely surgery coupled with interventions that augment myocardial metabolism and energetics may ameliorate both the prognosis of AS with HF and the prognosis of surgery.